Displacing the “inconvenient past”: the memory of repressions and genocides of the Soviet period in current Russia - Kamenskikh, Aleksey (Genocidas ir rezistencija, 2024)
The paper provides a review of the shifts occurring in politics of memory regarding the political repressions of the Soviet period within post-Soviet Russia, spanning from the early 1990s to the present day. Drawing on methodology of memorial politics studies offered by Jan Kubik and Michael Bernhard, and Aleida Assmann’s concepts of “canon” and “archive” of cultural memory, the author examines the dynamics of changes in this segment of Russia’s “memorial landscape” under the influence of political shifts associated with the aggressive actions of the Russian leadership in 2014 and 2022, regarding the displacement of memory about political crimes of the state from the public sphere as a form of the struggle of political elites against the opposite “counter-memory”. Particular attention is paid to the changes taking place in the politics of remembrance of Soviet political repression since the beginning of Russia’s full-scale invasion of Ukraine.
Keywords: Soviet political repressions; politics of memory; mnemonic actors; The Memorial Society